Repeated operations in patients with unsatisfactory results of celiac artery compression syndrome treatment - Z. Wan; A. M. Ignashov; I. P. Dudanov; V. N. Khirmanov; D. N. Doynikov; A. N. Morozov; A. Yu. Gichkin; S. D. Migashchuk; D. V. Kachalov; Yu. A. Ignashov; V. V. Ahmetov (Исследования и практика в медицине)
Purpose of the study. The reasons for the unsatisfactory results of surgical treatment of patients with celiac artery compression syndrome (CACS) and the role of repeated interventions allows to achieve a lasting improvement in most of them. The purpose of the study is to clarify the reasons for the unsatisfactory outcomes of surgical treatment of patients with CACS and the nature and significance of repeated operations.Patients and methods. From 860 patients with CASC who were operated on over the past 25 years 82 patients were selected with unsatisfactory treatment results. Initial conventional abdominal surgery was performed in 26 (31.7%) patients without a positive outcome before decompression of celiac artery (DCA). Primary operations were performed in 82 patients with proven CASC, of which 69 (84.1%) had DCA in open approach, isolated in 43 (52.4%) and combined in 26 (31.7%). Embolization of PDA aneurysm in one (1.2%) patient. In other medical institutions 15 (18.3%) patients were operated, among them 3 (3.7%) patients had DCA in open approach, in 4 (4.9%) laparoscopic DCA, in 6 (7.3%) angioplasty and emergency stenting and two (2.4%) reconstructive operations, all technically and clinically unsuccessful.Results. After DCA in open approach 51 (73.9%) patients of 69 patients had normal celiac artery flow. 4 patients had unresolved stenosis of the celiac artery and 15 relapsed its stenosis, one of them with residual stenosis after DCA twice, which amounted to 0.5% and 1.7%, respectively of 860 patients. Repeated operations were performed in 51 (62.2%) patients out of 82 to restore the celiac artery in 28 (34.2%), among them 4 (4.9%) in combination with interventions on the abdominal organs. Abdominal operations with concomitant diseases of the gastrointestinal tract with normal flow in celiac artery in 21 (25.6%).Scalenotomy in two (2.4%). Of 28 patients, re-revascularization of the celiac artery was successful as a result of open decompression in 7 out of 8, bypass surgery in 9 out of 10 and balloon angioplasty and with stenting in two out of 7. One had an effective primary DCA and the other resected PDA aneurysm. 19 patients out of 25 showed a good result after operations on the abdominal organs.Conclusion. The unsatisfactory results of surgical treatment of patients with CASC are associated with inadequate restoration of celiac artery restenosis and/or concomitant diseases of the abdominal organs. Repeated vascular operations are mainly: decompression of celiac artery in open approach, bypass surgery and balloon angioplasty and stenting, and/or abdominal mainly: cholecystectomy, NissenFP, and Strong surgery are of primary importance in the treatment of patients with CASC.